Sand grain electromagnetic parameter measuring method based on tabletting
Through the tablet-based electromagnetic parameter measurement method of sand particles, X-ray analysis technology and electromagnetic instruments are used to solve the inaccuracy of the measurement of electrical performance of sand particles in sand and dust weather, and achieve more stable and reliable test results, which are suitable for Stability assessment of power system.
Patent Information
- Application Number
- CN202411704186.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-10
AI Technical Summary
In sandy weather conditions, the electrical performance parameters of sand particles are difficult to accurately measure, resulting in unstable and inaccurate test results, which affects the evaluation of the stability of the power system.
The electromagnetic parameter measurement method of sand particles is used based on tablet pressing. The elemental components and material content of sand particles are analyzed by X-ray fluorescence spectrometer and X-ray photoelectron spectrometer. After the tablet is made, the electromagnetic parameters, including resistivity and dielectricity are measured. Constant, measured using an electrometer and an impedance analyzer.
It improves the accuracy and consistency of the measurement of electromagnetic parameters of sand particles, ensures the repeatability and reliability of test results, is suitable for laboratory and field environment monitoring, and provides more accurate data support.
Smart Images

Figure CN119290968A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder electromagnetic parameter testing, and in particular relates to a sand electromagnetic parameter measurement method based on tableting. Background Art
[0002] Under the current energy distribution and consumption pattern, there is a significant imbalance between energy resources and energy consumption centers. In order to optimize this configuration pattern, a large number of power transmission and transformation projects have to cross areas with complex and diverse geographical conditions, especially the high altitude, low rainfall and dry climate areas in the northwest. Compared with the plains with relatively superior geographical conditions, the northwest region faces more severe land desertification problems and frequent sandstorms.
[0003] Under dust weather conditions, charged sand particles in the air will significantly affect the distribution of the electric field in the surrounding space, causing electric field distortion and forming a high-intensity wind-sand electric field. This phenomenon poses a serious threat to the stable operation of the power system, especially in terms of the external insulation of transmission lines, whose safety and stability may be greatly reduced due to the effect of the wind-sand electric field.
[0004] In order to effectively deal with the impact of sandstorms on the external insulation performance of transmission lines, it is particularly important to conduct in-depth research on the electrical characteristics of sand particles in sandstorms. However, when simulating the movement of sand particles in sandstorms, the accurate measurement of the electrical performance parameters of sand particles has become a technical challenge. These key parameters, including resistivity, conductivity, dielectric constant, etc., are crucial to understanding the behavior of sand particles in an electric field.
[0005] However, when sand is used directly for testing under natural conditions, the test results often have large uncertainties due to factors such as the complexity of the sand surface and the uncontrollability of the test environment. In addition, even under the same test conditions, when the same batch of sand is retested for the second time, the results may be significantly different from the first measurement results. This instability of test results not only increases the difficulty of research, but also limits the reliability of research results in practical applications. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a method for measuring the electromagnetic parameters of sand particles based on a pressed sheet to solve the problem of inaccurate test results when measuring the electrical properties of sand particles in sandstorms in the prior art.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: A method for measuring electromagnetic parameters of sand particles based on tableting, comprising the following steps: S1, collecting sand samples from the area where the electromagnetic parameters of sand particles are to be measured, and analyzing the elemental composition and elemental content of the sand samples by X-ray fluorescence spectrometer; S2, obtaining the substances to which each element component belongs through X-ray photoelectron spectrometer; S3, converting the elemental content of the sand sample to obtain the content of the substance to which each elemental component belongs; S4, weighing the mixed substances based on the contents of the various substances in the obtained sand sample to prepare compressed tablets; S5, measuring electromagnetic parameters of the tablet.
[0008] A further improvement of the present invention is: Preferably, an ultra-high voltage direct current line is provided in the area where the electromagnetic parameters of the sand are to be measured.
[0009] Preferably, in S2, the X-ray photoelectron spectroscopy is used to separate the peaks of each elemental component to obtain the binding energy of the highest peak, and the substance to which each elemental component belongs is determined by the binding energy.
[0010] Preferably, in S3, the substance content of the substance is obtained based on the atomic weight of the element, the molecular weight of the substance and the element component content.
[0011] Preferably, in S3, the ratio of the atomic weight of the element component to the molecular weight of the substance to which it belongs is first obtained, and the mass of the substance to which it belongs is calculated in combination with the mass of the element.
[0012] Preferably, during the calculation process of S3, if an element belongs to two substances, the content of one of the substances is calculated first; the substance whose content is calculated first contains another element, and the other element only belongs to the substance whose content is calculated first.
[0013] Preferably, during the calculation process of S3, elements with a percentage content less than 1 are removed.
[0014] Preferably, S4, pressing the mixed powder of each substance into tablets by a tablet press.
[0015] Preferably, in S5, the electromagnetic parameters include resistivity and dielectric constant.
[0016] Preferably, the resistivity acquisition process is: obtaining the current-voltage curve of the pressed sheet by an electrometer, fitting to obtain the resistance value, and converting the resistance value into the resistivity; The dielectric constant was measured by an impedance analyzer.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for measuring electromagnetic parameters of sand grains based on tableting. The method aims at the technical problem that the electromagnetic parameters of fine mineral sand grains are difficult to accurately measure. First, the sand grains are subjected to elemental composition analysis to obtain the component content of sand in different regions. The constituent materials of sand grains in various places are obtained through the elemental composition. The corresponding compound powder is used for component simulation, and then the mixture obtained by component simulation is tableted to measure its electromagnetic parameters. In this method, the mixture is tableted using a powder tablet press, and the voltage-current curve of the disc is obtained using an electrometer, and the resistivity is obtained by calculation, and then the dielectric constant of the disc is measured using an impedance analyzer. The sand grains are pressed into sheets to reduce the dispersion and uneven distribution of the sand grains during the test process, thereby improving the accuracy and consistency of the measurement; through a standardized tableting method, the conditions of each test are ensured to be the same, thereby improving the repeatability and reliability of the test results; this method is not only suitable for laboratory research, but also can be applied to field environmental monitoring to provide more accurate data support for wind and sand projects.
[0018] Furthermore, during the measurement process, each elemental component is separated by peak processing through X-ray photoelectron spectroscopy to obtain the binding energy of the highest peak, and the substance to which each elemental component belongs is determined by the binding energy. The X-ray photoelectron spectrometer stores the binding energies of multiple substances, so the substance to which it belongs can be compared through the binding energy of the main peak.
[0019] Furthermore, if an element belongs to two substances at the same time, it is necessary to calculate the content of one of the substances first. The substance calculated first contains another element, and this other element only belongs to this substance in the entire sand composition system. Therefore, the content of this substance can be uniquely determined.
[0020] Furthermore, during the calculation process, elements with lower percentages are removed to reduce the calculation process.
[0021] Furthermore, the entire sample is made into a sheet to facilitate the measurement of various electromagnetic parameters. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a flow chart of a method for measuring electromagnetic parameters of sand particles based on tabletting of the present invention; Figure 2 It is the main peak of aluminum element measured in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with the accompanying drawings: In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0024] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0025] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0026] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0027] The present invention discloses a method for measuring electromagnetic parameters of sand particles based on tableting, comprising the following steps: S1, collect sand samples from the area where the electromagnetic parameters of sand particles are to be measured, and obtain the elemental composition and elemental content of the sand samples by X-ray fluorescence spectrometer analysis.
[0028] S2, based on the element content of the sand sample, obtain the substance to which each element belongs through X-ray photoelectron spectrometer; S3, the material content is obtained by converting the elemental composition content of the sample sand; During the S3 calculation process, elements with a percentage less than 1 are removed.
[0029] S4, based on the content of each substance in the obtained sand sample, samples are taken and made into tablets; S5, measuring electromagnetic parameters of the tablet.
[0030] In some implementation schemes of the present invention, in S1, the ground synthetic electric field test point of the ultra-high voltage direct current line is taken as the key investigation area, and the key area is taken as the area where the electromagnetic parameters of sand particles are to be measured. Sampling is carried out from this area so that the collected sand samples are representative and the point characteristics of the sand samples in this area can be determined.
[0031] In some embodiments of the present invention, in S1, an existing component analysis instrument - X-ray fluorescence spectrometer analysis (XRF) is used to analyze the composition of sand particles to obtain the element mass ratio and the element existence form, and all elements are listed. The working principle of X-ray fluorescence spectrometer (XRF) is based on the X-ray fluorescence phenomenon. When high-energy X-rays or gamma rays irradiate the material, secondary X-rays, i.e. X-ray fluorescence, are stimulated. When the atoms of each element are excited by high-energy radiation, they cause the transition of the inner electrons and emit X-rays with certain special wavelengths. The energy or wavelength characteristics of these X-rays are specific, so the types and contents of various elements in the sample can be identified by measuring the energy and quantity or wavelength of these emitted secondary X-rays.
[0032] In some embodiments of the present invention, in S2, each elemental component is subjected to peak separation by an X-ray photoelectron spectrometer (XPS) to obtain the binding energy of the highest peak, and the substance to which each elemental component belongs is determined by the binding energy. X-ray photoelectron spectrometer (XPS) is a method in which X-rays of a certain energy are irradiated onto the sample surface, interacting with the electrons in the sample to be tested, causing the electrons to be excited from the sample surface. These excited electrons are called photoelectrons. By measuring the energy of the photoelectrons, a photoelectron energy spectrum can be obtained, thereby obtaining the composition information of the object to be tested. In the XPS spectrum, the strongest photoelectron peak is the peak with the largest intensity, the smallest peak width and the best symmetry in the spectrum, which is called the main photoelectron peak of the element. Each element has a specific main photoelectron peak. Combined with the binding energy of each substance saved in XPS, it can be determined to which substance the element belongs after comparison.
[0033] Furthermore, in this step, it may be found that a certain substance belongs to two, three or more substances. In such cases, subsequent calculations are required to determine the content of the element in each substance.
[0034] In some embodiments of the present invention, during the calculation process of S3, the material content of the substance is obtained based on the atomic weight of the element, the molecular weight of the substance, and the element component content measured by XRF.
[0035] Specifically, the mass of the entire compound is derived based on the ratio of the atomic weight of the elemental component and the molecular weight of the substance to which it belongs.
[0036] Furthermore, in this process, if an element belongs to two substances, the content of one of the substances is calculated first; the substance whose content is calculated first contains another element, and the other element only belongs to the substance whose content is calculated first; based on the mass of the element in the substance and the total mass of the element, the content of the element in the other substance can be calculated.
[0037] In some embodiments of the present invention, during the calculation of S3, smaller values are eliminated and the component simulation is appropriately simplified to reduce the amount of calculation, such as eliminating elements with a percentage content of less than 1 in all components.
[0038] In some embodiments of the present invention, in S4, the substances are mixed and ground according to the mass ratio according to the content of each substance, and then the powder is pressed into a sheet by a tablet press. In this process, the substance to be measured is prepared into a round sheet, which can facilitate the subsequent measurement of electromagnetic parameters.
[0039] For example, for dielectric constant, it is usually based on the principle of parallel plate capacitors. Disc-shaped samples are easy to match with parallel plate capacitors to ensure the accuracy of measurement. For resistivity, it is convenient to measure resistivity through four-probe measurement technology, and it is also convenient to measure the corresponding voltage-current curve. The disc shape can reduce the impact of edge effects on measurement results. Edge effects may cause uneven current distribution, thereby affecting the measurement results of resistivity. The disc shape can reduce this unevenness and improve the accuracy of measurement.
[0040] In some embodiments of the present invention, the electromagnetic parameters include resistivity and dielectric constant. The resistivity is obtained by: obtaining the current-voltage curve of the pressed sheet by an electrometer, fitting the resistance value, converting the resistance value into resistivity, and measuring the dielectric constant by an impedance analyzer.
[0041] The following is further described in conjunction with specific embodiments.
[0042] Example 1 Step 1, sampling, survey key areas at the ground synthetic electric field test point of the UHV DC transmission line: divided into area 1~area 9, collect surface sand samples from the above areas for testing resistivity, conductivity and dielectric constant, the test method is the four-probe method, measuring resistivity and conductivity at 1MPa, 3MPa, 5MPa, 7MPa and 9MPa respectively, as shown in Table 1, it is found that the measurement results of area 2 and area 9 are quite different from the conventional data, at least two orders of magnitude different, so area 2 and area 9 are selected, and then a normal area is randomly selected for re-testing, Table 2 is obtained, and the results of the secondary measurement are obtained to exclude the problem of the measuring instrument. The dielectric parameters in Table 3 are obtained by one-time measurement.
[0043] Table 1. Primary measurement results
[0044] Table 2 Second retest results
[0045] Table 3 Dielectric constants
[0046] Step 2: Analyze the elemental composition and ingredients of the sand: Randomly select sand samples from five regions, use X-ray fluorescence spectrometer (XRF) and X-ray photoelectron spectroscopy (XPS) to analyze the elemental composition of the retrieved samples. The mass fraction of the element can be obtained from the XRF test results, and the existence form of the element can be inferred by analyzing the XPS spectrum. Taking aluminum as an example, Figure 2 As shown, the XPS spectrum of aluminum in the sample was separated using avantage software, and the binding energy corresponding to the highest peak obtained was consistent with the binding energy of aluminum silicate. Therefore, it can be inferred that the aluminum in the sample exists in the form of aluminum silicate. Similarly, the analysis results of XRF and XPS are combined to simulate the sand composition.
[0047] Furthermore, Si belongs to both aluminum silicate and SiO2. Since the aluminum element in aluminum silicate belongs only to aluminum silicate, the mass of aluminum silicate is first calculated based on the mass of aluminum element, and then the mass of silicon element therein is calculated by the mass of aluminum silicate. Further, the mass of silicon element in aluminum silicate is subtracted from the total mass of silicon element to obtain the mass of silicon element in SiO2.
[0048] Table 4 XRF test data
[0049] Table 5 XPS test data
[0050] Step 3, calculation, based on XRF test data, the mass ratio is assumed to be the mass of the element for calculation, the smaller data is discarded, all the retained data are added up, the sum is about 200, the obtained data is divided by 20 to obtain the data in Table 6. Since CaSO4 is hygroscopic, the data in Table 7 is used in the actual simulation, CaSO4 is discarded, and all Ca elements are represented by CaCO3.
[0051] Table 6: Sand composition simulation data
[0052] Table 7: Sand composition simulation experimental data
[0053] Step 4: Use the compound powders of the corresponding ingredients to mix and grind in proportion: Weigh the compound according to the table in step 3. After weighing one area, grind the powder with a mortar; use a tablet press to tablet the mixture: Use HY-15 powder tablet press for tableting. The powder is relatively loose. When adding powder to the upper end of the mold for the first time, you need to press the powder manually. Then continue to add powder to the upper end of the mold and use the tablet press to tablet. The tableting pressure should not be too large, about 4 tons. Excessive pressure is easy to produce fragments. The tablet press is also needed for demolding. Be careful when demolding. If the demolding pressure is too large, the tablets are easy to break.
[0054] Measure the electrical properties of the pressed sheet: Use an electrometer to measure the current-voltage curve, with a voltage setting range of 0-10V. Take 21 points within the setting range for measurement, draw the current-voltage curve, and fit the corresponding resistance value. Convert the resistance value to resistivity by calculation; Use an impedance analyzer to measure the dielectric constant, and compare the above data table 6 with the test results obtained in step 1.
[0055] Table 8 Electrical performance data measured by tableting
[0056] Combining Table 1, Table 2 and Table 3, and comparing Table 8, it is found that the resistivity of the pressed sheet is in the same order of magnitude as the resistivity obtained by directly testing the sand particles, and the dielectric constant data are also relatively consistent. The method of measuring the electromagnetic parameters of sand particles based on pressed sheets is reliable.
[0057] Based on the above analysis, it can be found that the method of the present invention is aimed at the technical problem that the electromagnetic parameters of fine mineral sand are difficult to accurately measure. First, the sand is analyzed for elemental composition to obtain the component content of sand in different regions. The constituent materials of sand in various places are obtained through the elemental composition. The corresponding compound powder is used for component simulation, and then the mixture obtained by component simulation is pressed into tablets to measure its electromagnetic parameters. In this method, the mixture is pressed into tablets using a powder tablet press, and the voltage-current curve of the disc is obtained using an electrometer. The resistivity is obtained by calculation, and then the dielectric constant of the disc is measured using an impedance analyzer. After comparing this method with the actual measurement results, it is found that the resistivity is in the same order of magnitude, and the dielectric constant data also meets the requirements. It can be preliminarily judged that the above method is reliable.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for measuring electromagnetic parameters of sand particles based on tableting, characterized in that: The following steps are involved: S1, collecting sand samples from the area where the electromagnetic parameters of sand particles are to be measured, and analyzing the elemental composition and elemental content of the sand samples by X-ray fluorescence spectrometer; S2, obtaining the substances to which each element component belongs through X-ray photoelectron spectrometer; S3, converting the elemental content of the sand sample to obtain the content of the substance to which each elemental component belongs; S4, weighing the mixed substances based on the contents of the various substances in the obtained sand sample to prepare compressed tablets; S5, measuring electromagnetic parameters of the tablet.
2. The method for measuring electromagnetic parameters of sand particles based on tableting according to claim 1, characterized in that: The area where the electromagnetic parameters of the sand particles are to be measured is provided with an ultra-high voltage direct current line.
3. The method for measuring electromagnetic parameters of sand particles based on tableting according to claim 1, characterized in that: In S2, the X-ray photoelectron spectroscopy processes the peaks of each elemental component to obtain the binding energy of the highest peak, and the substance to which each elemental component belongs is determined by the binding energy.
4. The method for measuring electromagnetic parameters of sand particles based on tableting according to claim 1, characterized in that: In S3, the material content of the substance is obtained based on the atomic weight of the element, the molecular weight of the substance and the element component content.
5. The method for measuring electromagnetic parameters of sand particles based on tableting according to claim 3, characterized in that: In S3, the ratio of the atomic weight of the element component to the molecular weight of the substance to which it belongs is first obtained, and the mass of the substance to which it belongs is calculated in combination with the mass of the element.
6. The method for measuring electromagnetic parameters of sand particles based on tableting according to claim 3, characterized in that: During the S3 calculation process, if an element belongs to two substances, the content of one of the substances is calculated first; if the substance whose content is calculated first contains another element, the other element only belongs to the substance whose content is calculated first.
7. The method for measuring electromagnetic parameters of sand particles based on tableting according to claim 1, characterized in that: During the S3 calculation process, elements with a percentage less than 1 are removed.
8. The method for measuring electromagnetic parameters of sand particles based on tableting according to claim 1, characterized in that: S4, pressing the mixed powder of each substance into tablets by a tablet press.
9. The method for measuring electromagnetic parameters of sand particles based on tableting according to any one of claims 1 to 7, characterized in that: In S5, the electromagnetic parameters include resistivity and dielectric constant.
10. The method for measuring electromagnetic parameters of sand particles based on tableting according to claim 9, characterized in that: The resistivity acquisition process is as follows: obtaining the current-voltage curve of the pressed sheet by an electrometer, fitting to obtain the resistance value, and converting the resistance value into the resistivity; The dielectric constant was measured by an impedance analyzer.